Total Count of Lactic Acid Bacteria in Goats and Cows Milk Yoghurt using Starter S. thermophilus RRAM-01, L. bulgaricus RRAM-01 and L. acidophilus IIA-2B4 - Olfa Mega; Jaya Putra Jahidin; Noraimah binti Sulaiman; Muhammad Yusuf; Muhamad Arifin; Irma Isnafia Arief (Buletin Peternakan, 2020)
Yoghurt is a well-known fermented dairy product which produced using a combination of lactic acid bacteria (LAB) of Streptococcus thermophilus, Lactobacillus bulgaricus and L. acidophillus as fermentation starters. Cow milk is usually used as a raw ingredient. The LAB-based local yoghurt starter (S. thermophilus RRAM-01 (ST), L. bulgaricus RRAM-01 (LB) and L. acidophilus IIA-2B4 (LA)) were previously isolated from milk and meat, nevertheless had not been extensively attempted to be used in yoghurt production. This study aimed to evaluate the characteristics of cow and goat milk based yoghurt produced by using a single local strater of S. thermophilus RRAM-01 (ST) or L. bulgaricus RRAM-01 (LB) or L. acidophilus IIA-2B4 (LA). The yoghurts were produced through addition of the starter (3% v/v each) with 1010 CFU mL-1 of initial population, and then fermented at room temperature for 24 hr.  The result revealed that initial population of LAB in goat’s milk yoghurt fermented by ST or LB were significantly higher than that of by LA. Yet, after 24-hour of storage at room temperature, the total population of LA increased and reached final population which was higher than LB or ST. Meanwhile, cow’s milk yoghurt fermented by LB had the highest population of at the initial day (D0), while after fermentation the highest population were observed on LB or LA cow’s milk yoghurt. Overall goat’s milk yoghurt had significantly lower pH values than the cow’s milk yoghurt. These were accompanied by higher the total titrated acid (TTA) of goat’s milk yoghurt than that of cow’s milk yoghurt. Based on pH and TAT values, it was found that  ST bacteria produced significantly higher total acidity goat’s milk yoghurt, followed by LB and LA. However, the type of culture had no effect on total acidity of cow's milk yoghurt.